The Oxford companion to fairy tales - Zipes, Jack (Oxford University Press, 2015)
In over 1,000 entries, this acclaimed Companion covers all aspects of the Western fairy tale tradition, from medieval to modern, under the guidance of Professor Jack Zipes. It provides an authoritative reference source for this complex and captivating genre, exploring the tales themselves, the writers who wrote and reworked them, and the artists who illustrated them. It also covers numerous related topics such as the fairy tale and film, television, art, opera, ballet, the oral tradition, music, advertising, cartoons, fantasy literature, feminism, and stamps. First published in 2000, 130 new entries have been added to account for recent developments in the field, including J. K. Rowling and Suzanne Collins, and new articles on topics such as cognitive criticism and fairy tales, digital fairy tales, fairy tale blogs and websites, and pornography and fairy tales. The remaining entries have been revised and updated in consultation with expert contributors. This second edition contains beautifully designed feature articles highlighting countries with a strong fairy tale tradition, covering: Britain and Ireland, France, Germany, Italy, Japan, North America and Canada, Portugal, Scandinavian countries, Slavic and Baltic countries, and Spain. It also includes an informative and engaging introduction by the editor, which sets the subject in its historical and literary context. A detailed and updated bibliography provides information about background literature and further reading material. In addition, the A to Z entries are accompanied by over 60 beautiful and carefully selected black and white illustrations. Already renowned in its field, the second edition of this unique work is an essential companion for anyone interested in fairy tales in literature, film, and art; and for anyone who values the tradition of storytelling
Includes bibliographical references (pages 669-720)
Keywords: Wörterbuch; Fairy tales / History and criticism; Fairy tales; Märchen